HBR's 10 must reads on managing yourself. (Boston : Harvard Business Review Press, 2010)
If you read nothing else on managing yourself, read these 10 articles (plus the bonus article (3z(BHow Will You Measure Your Life?" by Clayton M. Christensen). We've combed through hundreds of Harvard Business Review articles to select the most important ones to help you maximize yourself.s
Ch. 1. How will you measure your life? / Clayton M. Christensen -- Ch. 2. Managing oneself / Peter F. Drucker -- Ch. 3. Management time : who's got the monkey? / William Oncken and Donald L. Wass -- Ch. 4. How resilience work / Diane L. Coutu -- Ch. 5. Manage your energy, not your time / Tony Schwartz and Catherine McCarthy -- Ch. 6. Overloaded circuits / Edward M. Hallowell -- Ch. 7. Be a better leader, have a richer life / Stewart D. Friedman -- Ch. 8. Reclaim your job / Sumantra Ghoshal and Heike Bruch -- Ch. 9. Moments of greatness : entering the fundamental state / Robert E. Quinn -- Ch. 10. What to ask the person in the mirror / Robert S. Kaplan -- Ch. 11. Primal leadership : the hidden driver of great performance / Daniel Goleman, Richard Boyatzis and Annie McKee.
Includes index.
Keywords: Management; Success in business; Entrepreneurship -- Psychological aspects